Minimally invasive surgery. Issue 5 (25th April 2005) - Jaffray, B
Abstract : In 1987 Mouret performed the first laparoscopic cholecystectomy, starting a revolution in surgery. For paediatricians it is difficult to appreciate the magnitude of what has occurred in this short period. The development of minimal access techniques represents the most significant change in surgical practice since the introduction of aseptic technique or safe anaesthesia. As with many innovations, rapid change, technical language, and the evangelism of pioneers has left confusion in its wake.